2016
DOI: 10.1093/rpd/ncw346
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Monitoring of the Personnel at Radiation Hazardous Facilities

Abstract: The study of possible mechanisms resulting in changes in the immune system after exposure to ionizing radiation is an area that has not been thoroughly evaluated during recent years. This article presents an overview of immunological monitoring studies of personnel from the radiation-hazardous factories that took place over the past 20 years in Russia. The methodology of these studies is based on: (1) the preclinical evaluation of immune status of workers whose occupation involves potential exposure to ionizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Importantly, the study recorded not only basic laboratory changes in immune parameters but also clinically relevant symptomatic immune dysfunctions such as infections, allergies, autoimmunity and immunoproliferative diseases and found an increased risk for immune deficiency leading to an infectious syndrome in nuclear industry workers compared to controls. Significantly elevated IgE levels in a certain group of workers in the absence of a relevant allergic anamnesis was also reported, which might indicate a low dose radiation induced imbalance in humoral immunity ( Kiselev et al, 2017 ). Gyuleva et al basically confirmed most of these findings in Bulgarian nuclear power plant workers with additional details on individual lymphocyte subpopulations and their activation status.…”
Section: Human Biomonitoring and Epidemiological Data On Low Dose Radiation-induced Immunological Changesmentioning
confidence: 94%
“…Importantly, the study recorded not only basic laboratory changes in immune parameters but also clinically relevant symptomatic immune dysfunctions such as infections, allergies, autoimmunity and immunoproliferative diseases and found an increased risk for immune deficiency leading to an infectious syndrome in nuclear industry workers compared to controls. Significantly elevated IgE levels in a certain group of workers in the absence of a relevant allergic anamnesis was also reported, which might indicate a low dose radiation induced imbalance in humoral immunity ( Kiselev et al, 2017 ). Gyuleva et al basically confirmed most of these findings in Bulgarian nuclear power plant workers with additional details on individual lymphocyte subpopulations and their activation status.…”
Section: Human Biomonitoring and Epidemiological Data On Low Dose Radiation-induced Immunological Changesmentioning
confidence: 94%
“…En este estudio se encontró que el sistema inmunitario innato, las células natural killer y los neutrófilos, en particular, podrían activarse por la exposición crónica a aproximadamente 0,9 Gy de una manera dependiente de la dosis y de la tasa de dosis, lo que favorecía el mantenimiento de un estado inflamatorio crónico, que podría contribuir al desarrollo de patologías tardías relacionadas con la radiación como enfermedades cardiovasculares y malignas. En otros estudios similares, como el de Kiselev et al (15), llegaron a conclusiones muy similares, en donde revisaron los cambios inmunológicos en los trabajadores expuestos a radiación en un complejo químico siberiano (con más de 4000 trabajadores), en la instalación nuclear de Mayak y en la planta química y metalúrgica de Chepetsk. La característica común de estas instalaciones era la presencia de una exposición de tipo mixto (rayos gamma externos y radiación alfa interna debida al uranio incorporado).…”
Section: Síndrome Hematopoyéticounclassified
“…En nuestro país de acuerdo a lo consignado en el Título VII, Capítulo IV (vacaciones anuales remuneradas), Artículo 186, numeral 2 del Código sustantivo del trabajo "los profesionales y ayudantes que trabajan en establecimientos privados dedicados a la lucha contra la tuberculosis, y los ocupados en la aplicación de rayos X, tienen derecho a gozar de quince (15) días de vacaciones remuneradas por cada seis ( 6) meses de servicios prestados" (32), y se hace alusión al goce de vacaciones profilácticas las cuales tienen la finalidad de la separación temporal del trabajador frente a situaciones que signifiquen riesgo a la salud en materia laboral. En lo que respecta a la radiación ionizante es claro que es altamente peligrosa para un individuo trabajador, por lo que es fundamental el cumplimiento de las normas básicas de seguridad radiológica (24).…”
Section: Vacaciones Profilácticasunclassified